SELECTION OF COMPONENTS OF THE COMPOSITIONAL PROTEIN-CARBOHYDRATE MIXTURE TO IMPROVE THE QUALITY OF THE CHOPPED SEMI-FINISHED PRODUCTS - Taisa HONCHARENKO (Stefan cel Mare University of Suceava, 2019)
Meat is one of the most significant and nutritious foods available for the masses, which helps to satisfy most of the needs of the body. It has is a good source of proteins, zinc, iron, selenium, and phosphorus followed by vitamin A and B-complex vitamins. The modern production of meat products develops in the direction of expanding assortment of production, combining and optimizing the component composition in order to increase the nutritional value, substances by including in the recipe of the functional ingredients. The article presents the results of the study of qualitative indicators of animal origin protein preparations and protein-carbohydrate composition based on beef collagen protein and mixture of oilseed cultures flour for use in the recipe of chopped semi-finished products to improve their biological value. The aim of the study was to determine and compare the qualitative indicators of animal origin protein preparations, to create a compositional protein-carbohydrate mixture based on the selected animal protein and flour of oilseed cultures, to study its functional-technological properties in view of being used in the recipe of the chopped semi-finished products. Based on the study and comparative analysis of qualitative indicators of animal origin protein preparations, the use of Helios-11 beef collagen protein in the composition of a protein-carbohydrate composition was selected and substantiated. Ratios of protein and mixture of oilseed cultures flour (1: 4) have been determined, which create the most favorable conditions for the correction of meat systems by their functional-technological properties, providing an acceptable and stable level of emulsifying and water-binding properties.